Clinical and Laboratory Approaches to Selecting Antimicrobial Therapy for Peri-Implantitis Considering the Intrinsic Resistance of Pathogens - Bida, Олександр; Kostenko, Євген; Bida, Олексій (Actual Dentistry, 2026)
Relevance. Dental implantation is increasingly prioritized among methods of orthopedic rehabilitation for patients with partial tooth loss. One of the most common complications of dental implantation is peri-implantitis, which develops due to dysbiotic biofilm communities. To enable a personalized approach to peri-implantitis treatment, it is essential to establish an effective antimicrobial strategy that ensures adequate therapy and prolongs the functional lifespan of orthopedic structures. Microbiological screening in patients with peri-implantitis revealed microbial complexes from diverse taxonomic groups, each with varying intrinsic antibiotic susceptibility. Aim. To investigate the antibiotic resistance profiles of peri-implant microbiota under conditions of peri-implantitis, in the context of planning and implementing supportive pharmacological and non-pharmacological therapy of peri-implant tissues, as well as optimizing the oral microbiome during the use of orthopedic structures. Materials and methods. Antibiotic susceptibility was assessed using the disk diffusion method according to the recommendations of the European Committee on Antimicrobial Susceptibility Testing (EUCAST). Standard antibiotic disks manufactured by Pharmaktiv (Ukraine) were used. The sensitivity of bacterial isolates was tested against the following antibiotics (μg): amoxicillin/clavulanate (20/10), ceftriaxone (30), cefuroxime (50), cefoperazone/sulbactam (75), ceftazidime (30), cefotaxime (30), meropenem (10), imipenem (10), ciprofloxacin (5), levofloxacin (5), gatifloxacin (5), norfloxacin (10), ofloxacin (1), erythromycin (15), azithromycin (15), clarithromycin (15), lincomycin (15), clindamycin (10), doxycycline (30), cefixime (5). Results. When Streptococcus species were detected in the inflammatory focus, validation of susceptibility using screening antibiotics allowed tailoring antimicrobial therapy. Cephalosporins or beta-lactams were effective when strains were sensitive to these groups; in cases of resistance, fluoroquinolones remained the drugs of choice due to consistently high sensitivity. The study demonstrated that the microbial etiology of peri-implantitis involves complex interactions among diverse bacterial species and genera, including aerobic, anaerobic, and facultative anaerobic organisms, both gram-negative and gram-positive, complicating antibiotic selection. Antibiogram analysis of polymicrobial communities revealed significant variability in sensitivity within associations. Considering intrinsic resistance and comparing antibiograms across bacterial groups enables identification of an effective antibiotic targeting all dominant microbial complexes in the peri-implant area. Conclusions. Qualitative and quantitative analysis of the oral microbiota is a prerequisite for pre-implantation screening to establish a baseline microbial profile as a reference for future rehabilitation strategies. For personalized peri-implantitis treatment, it is crucial to detect and identify bacteria responsible for inflammation in order to design effective antimicrobial strategies, develop adequate treatment methods, and predict possible complications. Identification of the microbial profile with high accuracy will guide rational approaches to antimicrobial therapy in peri-implantitis.